MAIN PROBLEMS OF THE STRUCTURE OF A TOURIST DESTINATION (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
The work is a scientific substantiation of the territorial-forming role in the development of a tourist destination, according to which a logical transition is made from simple to complex, systemic. A system, in which all elements are in dialectical union with each other, interacting and mutually agreeing with each other. Each element has its specific place and role in the overall hierarchical system. The function of the tourism system is not only in hospitality, but also in solving the socio-economic, environmental problems of the area and, in general, in the targeted use of all natural, social, human (in capital terms) opportunities of the area, which requires: efficient use of the existing infrastructure, creation of a new, modern one; the development of the tourism economy of the region, the solution of socio-economic problems considered in one general context; ensuring sustainable human development based on sustainable tourism in the region. According to the results of the study, a tourist destination is a geographical area, where the driving force behind the organization and provision of public life is the tourism industry with its infrastructure.
Keywords: tourism; destination; organization; management; problem; ecology; hospitality; sustainable development; nature; economy